UPACARA BOKAS PADA ACARA PERKAWINAN UMAT HINDU KAHARINGAN DAYAK DUSUN (KAJIAN PENDIDIKAN AGAMA HINDU) - Derson Derson; I Gusti Agung Dharmawan; Tardi Edung (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
This study aims to explore and explain the religious meaning and educational value of the bokas ceremony at the Kaharingan Dayak Dusun Hindu wedding ceremony. The Bokas ceremony is part of the Pitra Yajna ceremony, which is a sacred offering to the ancestors by the Kaharingan Hindus. This research was conducted with a qualitative approach, in which data were obtained through interviews, observation and document recording which were then analyzed. As for the process before the bokas ceremony is carried out, then first carry out (1) bisik kurik event. (2) The process of Basantane or the proposal to bring goods. Meanwhile, the religious value of the tradition of the bokas paying hajat ceremony at the wedding ceremony is obligatory to be carried out by people who are bahajat parapah (asking for prayer) to the god kalalungan Aning kalelio. Bokas is a Pitra Yajna ceremony, which is an offering to ancestors. During the Bokas ceremony, a wadian Nayu calls Dewa Kallungan Aning Kalalio to come to receive offerings. If the bokas ceremony, at the wedding ceremony, deviates from what has been determined by Wadian Nayu, it can lead to elite bo'i, namely in the form of thunderstorms and accompanied by lightning that can turn humans into stone (curse). Meanwhile, the educational value reflected through the bokas ceremony is implemented in the concept of Tri Hita Karana and Tri Kaya Parisudha teachings.